Performance Evaluation and Slip Regulation Control of an Asymmetrical Parameter Type Two-Phase Induction Motor Drive Using a Three-Leg Voltage Source Inverter - Wekin Piyarat; Vijit Kinnares (My University, 2010)
This paper presents a performance evaluation and a simple speed control method of an asymmetrical parameter type two-phase induction motor drive using a three-leg VSI (Voltage Source Inverter). The two-phase induction motor is adapted from an existing single-phase induction motor resulting in impedance unbalance between main and auxiliary windings. The unbalanced two-phase inverter outputs with orthogonal displacement based on a SPWM (Sinusoidal Pulse Width Modulation) method are controlled with appropriate amplitudes for improving the motor performance. Dynamic simulation of the proposed drive system is given. A simple speed controller based on a slip regulation method is designed. The overall system is implemented on a DSP (Digital Signal Processor) board. The validity of the proposed system is verified by simulation and experimental results.
Keywords: Three-phase; Multilevel Inverters and Converters